Degree of tumor shrinkage following neoadjuvant chemoradiotherapy: a potential predictor for complete pathological response in esophageal cancer?. Issue 6 (2nd November 2012) - Voncken, F. E. M.; Jiang, H.; Kim, J.; Guindi, M.; Brierley, J.; Knox, J.; Liu, G.; Horgan, A. M.; Lister, J.; Darling, G.; Metser, U.; Wong, R. K. S.
Summary Neoadjuvant chemoradiotherapy (CRT) before surgery results in a pathological complete response (pCR) rate in about 1/3 of the patients, which is correlated with survival. It was hypothesized that volumetric tumor response to CRT would correlate with outcomes. Patients who completed trimodality therapy, where planning, pre‐, and post‐CRT computed tomography scans were available, and pathology was reviewed by a central pathologist, were eligible for analysis. Absolute and relative tumor volume change pretreatment and post‐treatment were correlated with pCR, locoregional recurrence (LRR), disease‐free survival, and overall survival. Fifty‐six patients were analyzed. pCR was observed in 30% of patients. Median follow up was 20.3 (range 4–89) months. The 2‐ and 4‐year overall survival was 61.3% (95% confidence interval [CI]: 45–74) and 25.0% (95%CI: 11–41); proportion disease free was 32.1% (95% CI: 19–46) and 20.6% (9–36) at 2 and 4 years, respectively. The median relative volume reduction was 17% (95% CI: −24, −3%). Using 20% as the criteria, the proportion of patients with pCR of ≥20% versus <20% was 13/25 (52%) versus 4/31 (13%) for those who did not (odds ratio 7.3; 95% CI: 2–27). The LRR at 2 and 4 years were 29.5% (95% CI: 16–43) and 36.2% (95% CI: 23–50). The relative tumor reduction ≥20% was significantly correlated with LRR (hazard ratio 0.24; 95% CI: 0.07–0.8; p 0.02) at 2 and 4 years, respectively. Relative tumor volume reduction following CRT is correlated with pCR and LRR. Further investigations are warranted to examine the effect of volume change, alone or in conjunction with other factors as potential predictors for pathological response.